KEBIJAKAN SISTEM TRANSPORTASI BARANG MULTIMODA DI PROVINSI NANGGROE ACEH DARUSSALAM - Sofyan M. Saleh; Ade Sjafruddin; Ofyar Z. Tamin; Russ Bona Frazila (Jurnal Transportasi, 2010)
More than 95% of freight movement in the Province of Aceh is done by the road mode. As most of the land in the province is surrounded by sea, the freight movement could have been done by sea transportation. Railway was already in the Province of Aceh long time ago, it began to operate in 1906, but the operation was closed in 1982. The Central Government and the Aceh Provincial Government want to revitalize the railway and there is also a plan to build a new Jalan Raya from Banda Aceh to North Sumatra border. However, there is a constraint in the costs of building these infrastructures so that multimodal and intermodal transportation can not take place. As a result, road transportation remains to be a major transport choice and this condition is even worse with vehicles on the road also tend to carry overload. This study was conducted in connection with the overload effect of the freight transport using trucks and how these trucks cause road deterioration and increase road maintenance costs in the Province of Aceh. The results suggest that multimodal/intermodal freight transportation, specifically road and railroad combined transport, could provide more efficient freight transport and, most likely, is the best option for the province.Keywords: freight transportation, multimodal/intermodal transportation, overload